Polyarylene sulfide resin composition, molded article, and method for producing same
Patent Information
- Application Number
- JP2024541843
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-03-02
- Filing Date
- 2024-02-15
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2044-02-15
AI Technical Summary
【0018】 本発明により、溶融成形時のドローリングを低減し、かつ、めっきの密着性に優れる成形品、当該成形品を提供可能な樹脂組成物を提供することができる。
Smart Images

Figure 0007639997000001 
Figure 0007639997000002 
Figure 0007639997000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyarylene sulfide resin composition, a molded article, and a method for producing the same. [Background technology]
[0002] Polyarylene sulfide (PAS) resins, such as polyphenylene sulfide (PPS), are excellent in mechanical strength, heat resistance, chemical resistance, moldability, dimensional stability, and flame retardancy, and are therefore increasingly being used in a variety of applications, primarily in electrical and electronic equipment parts and automotive parts. As the range of use expands, the demands on the quality and processability of PAS resins are increasing year by year.
[0003] Resin compositions containing PAS resins, which have a high melting point, low melt viscosity and are easy to flow, have high fluidity, and therefore often suffer from the problem of drooling (so-called "sagging" or "snot dripping") from the tip of the cylinder nozzle of the molding machine during melt molding such as injection molding, extrusion molding, etc. However, since highly functional molded products have complex mold structures, there was an issue that reducing the fluidity of the resin composition would result in poor processability.
[0004] Another cause of such drooling is the gasification of low-volatile components contained in the resin composition, and therefore attempts have been made to reduce drooling by reducing the amount of generated gas. For example, Patent Document 1 describes a glass fiber surface-treated with a sizing agent containing PAS, an epoxy resin, a urethane resin, and a silane coupling agent, 0.5 to 3 parts by weight of a silane coupling agent having at least one functional group selected from the group consisting of amino groups and epoxy groups, and a pore diameter of 4 to 10 Å, a specific surface area of 200 m 2 A technique for blending a synthetic zeolite having a molecular weight of 0.1 to 1.0 μm is disclosed.
[0005] In recent years, in response to demand for high functionality in materials and products, multi-materialization, in which new composite parts are manufactured by integrating different materials such as resins and metals according to the required characteristics of each part or section, is becoming widespread as a very effective method. When a metal film must be formed on the surface of a molded product, for example when used for electronic circuits, wiring connectors, etc., there was a problem that the metal film easily peeled off even if a roughening treatment was applied to the surface and a metal film was formed, because the PAS resin composition or its molded product has poor adhesion (difficult to adhere).
[0006] As a method for solving the above problem, a method has been proposed in which the surface of a PAS molded product is etched with an etching solution, a palladium catalyst is applied, and then electroless copper plating is performed to form a copper plating layer (see, for example, Patent Document 2), but the adhesion of the plating is insufficient. Also, a method has been proposed in which voids are formed on the surface of a molded product during etching by blending a hydrolyzable resin with a carbonate and a polyolefin wax (see, for example, Patent Document 3). However, in this method, gas generated from the hydrolyzable resin etc. may promote drooling. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2016-132710 A [Patent Document 2] Japanese Patent Publication No. 14880 / 1983 [Patent Document 3] International Publication No. 2021 / 106974 Brochure Summary of the Invention [Problem to be solved by the invention]
[0008] With these conventional techniques, it is difficult to reduce the drowning property while maintaining the fluidity (processability) during melt molding, and it has not been possible to obtain a PAS resin composition or molded product that achieves excellent plating adhesion.
[0009] In view of the above, an object of the present invention is to provide a molded article which reduces drooling during melt molding and has excellent plating adhesion, and a resin composition capable of providing such a molded article. [Means for solving the problem]
[0010] As a result of intensive research aimed at solving the above problems, the present inventors have discovered that by blending calcium carbonate having a specific particle size as an inorganic filler, the amount of drowning in the resulting PAS resin composition is reduced and further the resulting molded article has excellent plating adhesion, thereby completing the present invention.
[0011] That is, the present disclosure provides a PAS resin composition comprising a PAS resin (A) and an inorganic filler (B) as essential components, The inorganic filler (B) is calcium carbonate surface-coated with a silane coupling agent or an inorganic acid, and the cumulative 90% particle diameter of the particle size distribution (D 90 ) is 3 μm or less, The present invention relates to a PAS resin composition, in which the blending amount of the inorganic filler (B) is 50 to 150 parts by mass per 100 parts by mass of the PAS resin (A).
[0012] The present disclosure also relates to a molded article obtained by melt molding the above-described resin composition.
[0013] The present disclosure also relates to a laminate in which a plating layer is laminated on a surface of the above-described molded article.
[0014] The present disclosure also provides a method for producing a PAS resin mixture, comprising a step of blending a PAS resin (A) and an inorganic filler (B) as essential components, and melt-kneading the mixture at a temperature range equal to or higher than the melting point of the PAS resin (A), The inorganic filler (B) is calcium carbonate surface-coated with a silane coupling agent or an inorganic acid, and the cumulative 90% particle diameter of the particle size distribution (D 90 ) is 3 μm or less, The present invention relates to a method for producing a PAS resin composition, wherein the blending amount of the inorganic filler (B) is 50 to 150 parts by mass per 100 parts by mass of the PAS resin (A).
[0015] The present disclosure also relates to a method for producing a molded article, comprising the steps of producing a PAS resin composition by the above-described production method and melt-molding the resulting PAS resin composition.
[0016] The present disclosure also relates to a method for producing a laminate, comprising the steps of producing a PAS resin molded article by the above-described manufacturing method and plating the surface of the obtained molded article.
[0017] In the present invention, the joining of the surface of the PAS resin molded article and the plating layer to each other is expressed as adhesion or adhesion. Effect of the Invention
[0018] According to the present invention, it is possible to provide a molded article which reduces drooling during melt molding and has excellent plating adhesion, and a resin composition capable of providing such a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] An embodiment of the present disclosure will be described in detail below, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made without departing from the spirit of the present disclosure. In addition, when multiple upper and lower limit values are described for a specific parameter, any upper and lower limit values can be combined to form a suitable numerical range.
[0020] <Resin composition> The resin composition according to the present embodiment is a PAS resin composition comprising a PAS resin (A) and an inorganic filler (B) as essential components, the inorganic filler (B) being calcium carbonate surface-coated with a silane coupling agent or an inorganic acid, and a cumulative 90% particle diameter (D 90) is 3 μm or less, and the compounding amount of the inorganic filler (B) is 50 to 150 parts by mass with respect to 100 parts by mass of the PAS resin (A). This will be described in detail below.
[0021] <PAS resin (A)> The PAS resin composition according to this embodiment is prepared by blending a PAS resin as an essential component.
[0022] The PAS resin has a resin structure having a structure in which an aromatic ring and a sulfur atom are bonded as a repeating unit. Specifically, the following general formula (1)
[0023]
Chemical formula
[0024]
Chemical formula
[0025] Here, in the structural part represented by the general formula (1), particularly, R1 and R2 in the formula are preferably hydrogen atoms from the viewpoint of the mechanical strength of the PAS resin. In that case, those bonded at the para position represented by the following formula (3) and those bonded at the meta position represented by the following formula (4) are exemplified.
[0026]
Chemical formula
[0027] The PAS resin may include not only the structural moieties represented by the general formula (1) or (2) but also the structural moieties represented by the following structural formulae (5) to (8):
[0028] [ka] The structural moieties represented by the general formulae (1) and (2) may account for 30 mol % or less of the total of the structural moieties represented by the general formulae (1) and (2). In particular, in the present disclosure, it is preferable that the structural moieties represented by the general formulae (5) to (8) account for 10 mol % or less in terms of the heat resistance and mechanical strength of the PAS resin. When the PAS resin contains the structural moieties represented by the general formulae (5) to (8), the bonding mode thereof may be either a random copolymer or a block copolymer.
[0029] The PAS resin may have naphthyl sulfide bonds or the like in its molecular structure, but the amount of such bonds is preferably 3 mol % or less, and particularly preferably 1 mol % or less, relative to the total number of moles including other structural portions.
[0030] The physical properties of the PAS resin are not particularly limited as long as they do not impair the effects of the present invention, but are as follows.
[0031] (Melt Viscosity) The melt viscosity of the PAS resin used in the present disclosure is not particularly limited as long as it does not impair the effects of the present invention, but in order to achieve a good balance between fluidity and mechanical strength, the melt viscosity (V6) measured at 300°C is preferably in the range of 2 to 500 Pa·s, more preferably in the range of 5 to 200 Pa·s, even more preferably in the range of 5 to 100 Pa·s, and particularly preferably in the range of 5 to 50 Pa·s. However, the melt viscosity (V6) is measured using a Shimadzu flow tester, CFT-500D, at 300°C, load: 1.96×10 6The melt viscosity is measured after holding the sample for 6 minutes at a pressure of 1 Pa and L / D = 10 (mm) / 1 (mm).
[0032] (Non-Newtonian Exponents) The non-Newtonian index of the PAS resin used in the present disclosure is not particularly limited as long as it does not impair the effects of the present invention, but is preferably in the range of 0.90 or more to 2.00 or less. When a linear PAS resin is used, the non-Newtonian index is preferably in the range of 0.90 or more, more preferably 0.95 or more, and preferably 1.50 or less, more preferably 1.20 or less. Such a PAS resin is excellent in mechanical properties, fluidity, and abrasion resistance. However, in the present disclosure, the non-Newtonian index (N value) is a value calculated using the following formula by measuring the shear rate (SR) and shear stress (SS) using a capillary rheometer under the conditions of a melting point of +20°C and a ratio of the orifice length (L) to the orifice diameter (D) of L / D=40. The closer the non-Newtonian index (N value) is to 1, the closer the structure is to a linear structure, and the higher the non-Newtonian index (N value), the more branched the structure is.
[0033]
number
[0034] (Weight average molecular weight) The weight average molecular weight of the PAS resin used in this embodiment is not particularly limited as long as it does not impair the effects of the present invention, but is preferably 10,000 to 80,000, and more preferably 12,500 to 60,000. The weight average molecular weight of the PAS resin of the present disclosure is the weight average molecular weight measured using gel permeation chromatography under the following measurement conditions. Six types of monodisperse polystyrene are used for calibration. Equipment: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000, manufactured by Senshu Scientific Co., Ltd.) Column: UT-805L (Showa Denko K.K.) Column temperature: 210℃ Solvent: 1-chloronaphthalene Measurement method: UV detector (360 nm)
[0035] (Manufacturing method) The method for producing the PAS resin is not particularly limited, but examples thereof include (production method 1) a method in which a dihalogeno aromatic compound is polymerized in the presence of sulfur and sodium carbonate, and if necessary, a polyhalogeno aromatic compound or other copolymerization component is added, (production method 2) a method in which a dihalogeno aromatic compound is polymerized in a polar solvent in the presence of a sulfidizing agent or the like, and if necessary, a polyhalogeno aromatic compound or other copolymerization component is added, (production method 3) a method in which p-chlorothiophenol is added, and if necessary, other copolymerization components are added, and self-condensation is performed, and (production method 4) a method in which a diiodo aromatic compound and elemental sulfur are melt-polymerized under reduced pressure in the presence of a polymerization inhibitor that may have a functional group such as a carboxy group or an amino group. Among these methods, (production method 2) is preferred because it is versatile. During the reaction, an alkali metal salt of a carboxylic acid or sulfonic acid or an alkali hydroxide may be added to adjust the degree of polymerization. Among the above-mentioned (Production Method 2) methods, there is a method for producing a PAS resin by introducing a water-containing sulfidizing agent into a mixture containing a heated organic polar solvent and a dihalogeno aromatic compound at a rate at which water can be removed from the reaction mixture, and reacting the dihalogeno aromatic compound and the sulfidizing agent in the organic polar solvent, and optionally adding a polyhalogeno aromatic compound, and controlling the amount of water in the reaction system to within a range of 0.02 to 0.5 mol per mol of the organic polar solvent (see JP-A-07-228699). Particularly preferred is a method in which a dihalogenoaromatic compound and, if necessary, a polyhalogenoaromatic compound or other copolymerization component are added in the presence of an alkali metal sulfide and an aprotic polar organic solvent, and an alkali metal hydrosulfide and an organic acid alkali metal salt are reacted while controlling the organic acid alkali metal salt in the range of 0.01 to 0.9 mol per mol of the sulfur source and the amount of water in the reaction system to be 0.02 mol or less per mol of the aprotic polar organic solvent (see WO2010 / 058713 pamphlet).Specific examples of the dihalogenoaromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-di Examples of the polyhalogeno aromatic compounds include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, 1,4,6-trihalonaphthalene, etc. The halogen atoms contained in the above compounds are preferably chlorine atoms or bromine atoms.
[0036] The method for post-treating the reaction mixture containing the PAS resin obtained by the polymerization step is not particularly limited, but for example, (post-treating 1) after the completion of the polymerization reaction, first, the solvent is distilled off under reduced pressure or normal pressure, either as is or after the addition of an acid or base, and then the solid matter remaining after the solvent distillation is washed once or twice or more times with a solvent such as water, the reaction solvent (or an organic solvent having a similar solubility to the low molecular weight polymer), acetone, methyl ethyl ketone, or alcohols, and then neutralized, washed with water, filtered, and dried; or (post-treating 2) after the completion of the polymerization reaction, the reaction mixture is dissolved in a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, or aliphatic hydrocarbons (soluble in the polymerization solvent used and poorly soluble in at least PAS). or (post-treatment 3) a method in which, after the completion of the polymerization reaction, a reaction solvent (or an organic solvent having a solubility equivalent to that of the low molecular weight polymer) is added to the reaction mixture, the mixture is stirred, the mixture is filtered to remove the low molecular weight polymer, the mixture is washed once or twice or more times with a solvent such as water, acetone, methyl ethyl ketone, or an alcohol, and then the mixture is neutralized, washed with water, filtered, and dried; (post-treatment 4) a method in which, after the completion of the polymerization reaction, water is added to the reaction mixture, the mixture is washed with water, filtered, and if necessary, an acid is added during the water washing to perform an acid treatment, and then the mixture is dried; or (post-treatment 5) a method in which, after the completion of the polymerization reaction, the reaction mixture is filtered, and if necessary, the mixture is washed once or twice or more times with the reaction solvent, and then the mixture is washed with water, filtered, and dried.
[0037] In the post-treatment methods exemplified above in (Post-treatment 1) to (Post-treatment 5), the PAS resin may be dried in a vacuum, or in air or in an inert gas atmosphere such as nitrogen.
[0038] <Inorganic filler (B)> The PAS resin composition according to the present embodiment contains, in addition to the above-mentioned PAS resin (A), an inorganic filler (B) having a cumulative 90% particle diameter of the particle size distribution (D 90The present invention is made by blending calcium carbonate (hereinafter simply referred to as "calcium carbonate"), which has a surface coating with a silane coupling agent or an inorganic acid and has a particle size of 3 μm or less, as an essential component.
[0039] In addition, the inorganic filler (B) applicable to this embodiment has a cumulative 90% particle diameter of the particle size distribution (D 90 ), cumulative 50% particle diameter (D 50 ) and cumulative 10% particle size (D 10 ) to obtain the following formula (1): (D 90 -D 10 ) / D 50 <2.0 … (1) In this range, the obtained molded article has better plating adhesion. The particle size distribution is a particle size distribution measured by a laser diffraction scattering type particle size distribution measuring instrument (Microtrac MT3300EXII) in accordance with a conventional method, and D 90 , D 50 , D 10 is a value calculated from the particle size distribution.
[0040] Calcium carbonate can be broadly divided into natural products that are naturally produced as limestone and synthetic products obtained by chemical synthesis. There are no particular limitations on the calcium carbonate that can be applied to this embodiment as long as it does not impair the effects of the present invention, but synthetic products are preferred because they have a uniform particle shape and contain fewer impurities, and in particular, those synthesized by the carbon dioxide gas method, in which quicklime is reacted with carbon dioxide gas, are preferred. As for the crystal form, calcite crystals are preferred from the viewpoint of heat resistance.
[0041] The inorganic filler (B) applicable to this embodiment is surface-treated with a silane coupling agent or inorganic acid for the purpose of improving dispersibility.The silane coupling agent is not particularly limited as long as it does not impair the effect of the present invention, but the silane coupling agent having a functional group that reacts with a carboxyl group, such as an epoxy group, an isocyanato group, an amino group or a hydroxyl group, is preferably mentioned. Examples of such silane coupling agents include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane. The inorganic acid is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include orthophosphoric acid, acidic phosphoric acid esters, polyphosphoric acids such as condensed phosphoric acids such as hexametaphosphoric acid and pyrophosphoric acid, and salts thereof. Among these, when calcium carbonate surface-coated with at least one of an amino group-containing alkoxysilane compound, an epoxy group-containing alkoxysilane compound, and calcium phosphate is used, it is preferable because it has excellent drawability during melt molding due to interaction with the terminal functional group of the PAS resin and inorganic fillers such as glass fiber.
[0042] Moreover, from the viewpoint of processability, the inorganic filler (B) applicable to the present embodiment preferably has a mass loss rate of 1% by mass or less at 100 to 350° C. The mass loss rate in the present disclosure is a value calculated from a measured value when heated from 23° C. to 350° C. at 10° C. / min in an oxygen atmosphere using a thermogravimetric analyzer (TGA). A mass loss rate within this range is preferable because it provides excellent resistance to rolling during melt molding.
[0043] The blending ratio of the inorganic filler (B) is 50 to 150 parts by mass, preferably 60 to 120 parts by mass, and more preferably 60 to 100 parts by mass, per 100 parts by mass of the PAS resin (A) in order to further improve the adhesive strength with the plated layer formed by the plating treatment. If the blending amount is less than this range, the plating adhesion becomes poor, and furthermore, the amount of drooling may increase.
[0044] (Silane coupling agent) If necessary, a silane coupling agent can be blended as an optional component in the PAS resin composition according to this embodiment for the purpose of improving mechanical properties.
[0045] Here, the silane coupling agent having the functional group is not particularly limited as long as it does not impair the effects of the present invention, but preferred examples include silane coupling agents having a functional group that reacts with a carboxy group, such as an epoxy group, an isocyanato group, an amino group, or a hydroxyl group. Examples of such silane coupling agents include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.
[0046] In addition, the content of the silane coupling agent having the functional group in the PAS resin composition of the present invention is not particularly limited, but from the viewpoint of obtaining better moist heat resistance and mechanical strength, it is preferably 0.3 parts by mass or more per 100 parts by mass of the PAS resin, more preferably 0.4 parts by mass or more, and even more preferably 0.5 parts by mass or more.
[0047] (Elastomer) The PAS resin composition according to the present embodiment may contain an elastomer as an optional component, if necessary, for the purpose of improving mechanical properties. By further including the elastomer, the toughness and cold and thermal shock resistance of the PAS resin composition can be further improved. In addition, the adhesion of plating on the laminate can be further improved. From the same viewpoint, it is preferable to use a thermoplastic elastomer as the elastomer.
[0048] The thermoplastic elastomer may be a polyolefin elastomer, a fluorine elastomer, or a silicone elastomer, among which a polyolefin elastomer is preferred. When these elastomers are added, the amount of the elastomer is not particularly limited, but is preferably 0.01 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, and even more preferably 1 to 15 parts by mass, relative to 100 parts by mass of the PAS resin (A). In this range, the flexibility of the resulting PAS resin composition is improved, which is preferable. If the amount of the elastomer exceeds this range, the rolling property of the resin composition may deteriorate.
[0049] Examples of the polyolefin-based elastomer include homopolymers of α-olefins, copolymers of two or more α-olefins, and copolymers of one or more α-olefins and vinyl polymerizable compounds having functional groups. In this case, examples of the α-olefins include α-olefins having 2 or more to 8 or less carbon atoms, such as ethylene, propylene, and 1-butene. Examples of the functional groups include carboxy groups, acid anhydride groups (-C(=O)OC(=O)-), epoxy groups, amino groups, hydroxyl groups, mercapto groups, isocyanate groups, and oxazoline groups. Examples of the vinyl polymerizable compound having the functional group include one or more of vinyl acetate, α,β-unsaturated carboxylic acids such as (meth)acrylic acid, alkyl esters of α,β-unsaturated carboxylic acids such as methyl acrylate, ethyl acrylate, and butyl acrylate, metal salts of α,β-unsaturated carboxylic acids such as ionomers (metals include alkali metals such as sodium, alkaline earth metals such as calcium, and zinc, etc.), glycidyl esters of α,β-unsaturated carboxylic acids such as glycidyl methacrylate, α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid, and derivatives of the α,β-unsaturated dicarboxylic acids (monoesters, diesters, and acid anhydrides). The above-mentioned thermoplastic elastomers may be used alone or in combination of two or more.
[0050] (Other inorganic fillers) The PAS resin composition according to the present embodiment may further contain an inorganic filler other than the calcium carbonate (hereinafter, referred to as "other filler"). By further containing the inorganic filler, the mechanical strength and thermal conductivity of the PAS resin composition can be further increased.
[0051] Here, as the other filler, a known and commonly used material can be used as long as it does not impair the effect of the present invention, and examples thereof include fillers of various shapes such as granular and plate-shaped ones. For example, fibrous fillers such as glass fiber, carbon fiber, silane glass fiber, ceramic fiber, aramid fiber, metal fiber, potassium titanate, silicon carbide, calcium silicate, wollastonite, and natural fibers can be used, and non-fibrous fillers such as glass beads, glass flakes, barium sulfate, clay, pyrophyllite, bentonite, sericite, mica, talc, attapulgite, ferrite, calcium carbonate, magnesium carbonate, zeolite, milled fiber, and calcium sulfate can be used. In addition, these other fillers can be surface-treated, and if necessary, epoxy compounds, isocyanate compounds, silane compounds, titanate compounds, borane treatment, ceramic coating, etc. can be applied.
[0052] The content of the other filler is not particularly limited, but from the viewpoint of better mechanical properties and dimensional stability, it is preferably 5 to 350 parts by mass, more preferably 10 to 300 parts by mass, and even more preferably 20 to 250 parts by mass relative to 100 parts by mass of the PAS resin.
[0053] In the PAS resin composition according to this embodiment, the content of the inorganic filler (B) and other fillers combined (hereinafter sometimes referred to as "total inorganic filler") is not particularly limited, but from the viewpoint of excellent isothermal crystallization rate of the resin composition, for example, it is preferably 20 parts by mass or more, more preferably 25 parts by mass or more, and even more preferably 30 parts by mass or more, per 100 parts by mass of the total amount of the PAS resin and the total inorganic fillers. This is because within such a range, the isothermal crystallization time becomes short and good moldability is exhibited.
[0054] Furthermore, in addition to the above components, the PAS resin composition according to the present embodiment may further contain synthetic resins such as polyester resin, polyamide resin, polyimide resin, polyetherimide resin, polycarbonate resin, polyphenylene ether resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylate resin, polyethylene resin, polypropylene resin, polytetrafluoroethylene resin, polydifluoroethylene resin, polystyrene resin, ABS resin, epoxy resin, phenol resin, urethane resin, and liquid crystal polymer as optional components depending on the application. In particular, it is preferable to add a fluorine-based resin because it improves the sliding properties. In the present disclosure, the synthetic resin is not an essential component, but when it is added, the ratio of the synthetic resin is not particularly limited as long as it does not impair the effects of the present invention, and it differs depending on each purpose and cannot be generally defined, but the ratio of the synthetic resin to be added in the resin composition according to the present disclosure may be, for example, about 5 to 15 parts by mass relative to 100 parts by mass of the PAS resin (A).
[0055] In addition, the PAS resin composition according to the present embodiment may contain other known and commonly used additives as optional components, such as colorants, antistatic agents, antioxidants, heat stabilizers, UV stabilizers, UV absorbers, foaming agents, flame retardants, flame retardant assistants, rust inhibitors, and release agents (metal salts or esters of fatty acids having 18 to 30 carbon atoms, including stearic acid or montanic acid, polyolefin waxes such as polyethylene, etc.) as needed. These additives are not essential components, and may be used in an amount of, for example, preferably 0.01 parts by mass or more, and preferably 1000 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 10 parts by mass or less, based on 100 parts by mass of the PAS resin (A), as appropriate for the purpose or use so as not to impair the effects of the present invention.
[0056] The resin composition according to the present embodiment has excellent resistance to drooling during molding. Note that the drooling in the present disclosure refers to a defect in which a molten resin composition leaks out from the tip of the nozzle of an injection molding machine during injection molding, and was evaluated by the method described in the examples.
[0057] <Method of producing resin composition> The method for producing a PAS resin composition according to this embodiment includes a step of blending the essential components and melt-kneading them in a temperature range equal to or higher than the melting point of the PAS resin (A). More specifically, the PAS resin composition according to this embodiment is composed of the essential components and, if necessary, other optional components. The method for producing the resin composition used in this disclosure is not particularly limited, but examples thereof include a method of blending the essential components and, if necessary, the optional components, and melt-kneading them, and more specifically, a method of uniformly dry-mixing them in a tumbler or Henschel mixer, if necessary, and then feeding them into a twin-screw extruder and melt-kneading them.
[0058] The melt kneading can be carried out by heating the resin to a temperature range in which the resin temperature is equal to or higher than the melting point of the PAS resin (A), preferably equal to or higher than the melting point + 10°C, more preferably equal to or higher than the melting point + 10°C, even more preferably equal to or higher than the melting point + 20°C, preferably equal to or lower than the melting point + 100°C, more preferably equal to or lower than the melting point + 50°C.
[0059] The melt kneader is preferably a twin-screw kneading extruder from the viewpoint of dispersibility and productivity. For example, it is preferable to melt knead while appropriately adjusting the discharge amount of the resin component in the range of 5 to 500 (kg / hr) and the screw rotation speed in the range of 50 to 500 (rpm), and it is more preferable to melt knead under the condition that the ratio (discharge amount / screw rotation speed) is in the range of 0.02 to 5 (kg / hr / rpm). In addition, the addition and mixing of each component to the melt kneader may be performed simultaneously or in portions. For example, when other fibrous fillers are added as necessary among the components, it is preferable to feed them into the extruder from the side feeder of the twin-screw kneading extruder from the viewpoint of dispersibility. The position of the side feeder is preferably such that the ratio of the distance from the extruder resin input part (top feeder) to the side feeder to the total screw length of the twin-screw kneading extruder is 0.1 or more, more preferably 0.3 or more. In addition, such a ratio is preferably 0.9 or less, more preferably 0.7 or less.
[0060] The PAS resin composition according to the present disclosure obtained by melt kneading in this manner is a molten mixture containing the essential components, optional components added as necessary, and components derived therefrom. Therefore, the PAS resin composition according to the present disclosure has a morphology in which the PAS resin (A) forms a continuous phase and other essential components and optional components are dispersed. After the melt kneading, the PAS resin composition according to the present disclosure is preferably processed into pellets, chips, granules, powder, or other forms by a known method, for example, by extruding the molten resin composition into a strand shape, and then pre-dried at a temperature range of 100 to 150°C as necessary.
[0061] <Molded products and manufacturing methods for molded products> The molded article according to this embodiment is obtained by melt molding the PAS resin composition. The manufacturing method of the molded article according to this embodiment includes a step of melt molding the PAS resin composition obtained by the manufacturing method described above. Therefore, the molded article according to this embodiment has a morphology in which the PAS resin (A) forms a continuous phase and other essential components and optional components are dispersed. The PAS resin composition having such a morphology allows the molded article to have excellent mechanical strength.
[0062] The PAS resin composition according to the present embodiment can be subjected to various molding processes such as injection molding, compression molding, extrusion molding of composites, sheets, pipes, pultrusion molding, blow molding, and transfer molding, but is particularly suitable for injection molding because of its excellent releasability. When molding by injection molding, various molding conditions are not particularly limited, and molding can be performed by a normal general method. For example, in an injection molding machine, the PAS resin composition is melted at a resin temperature in a temperature range of the melting point of the PAS resin (A) or higher, preferably in a temperature range of the melting point +10°C or higher, more preferably in a temperature range of the melting point +10°C to the melting point +100°C, and even more preferably in a temperature range of the melting point +20 to the melting point +50°C, and then the resin is injected into a mold from a resin discharge port and molded. At that time, the mold temperature may also be set to a known temperature range, for example, room temperature (23°C) to 300°C, preferably 130 to 190°C.
[0063] The method for producing a molded article according to this embodiment may include a step of annealing the molded article. The optimum conditions for the annealing treatment are selected depending on the application or shape of the molded article, and the annealing temperature is in a temperature range equal to or higher than the glass transition temperature of the PAS resin (A), preferably in a temperature range equal to or higher than the glass transition temperature +10°C, and more preferably in a temperature range equal to or higher than the glass transition temperature +30°C. On the other hand, it is preferably in a range of 260°C or lower, and more preferably in a range of 240°C or lower. The annealing time is not particularly limited, but is preferably in a range of 0.5 hours or higher, and more preferably in a range of 1 hour or higher. On the other hand, it is preferably in a range of 10 hours or lower, and more preferably in a range of 8 hours or lower. In such a range, not only the distortion of the molded article obtained is reduced and the crystallinity of the resin is improved, but also the thermal conductivity, mechanical properties, and fuel barrier properties are further improved, which is preferable. The annealing treatment may be performed in air, but is preferably performed in an inert gas such as nitrogen gas.
[0064] The molded article according to the present embodiment includes a remolded article obtained by reusing a molded article obtained by melt-molding the PAS resin composition. Specifically, for example, the molded article includes a sprue or runner generated during the manufacture of a molded article, a molded article recovered as a non-standard molded article, or a molded article once used as a product, which is washed as necessary, crushed, and melt-molded again at a temperature equal to or higher than the melting point of the PAS resin. When reusing, it is preferable from the viewpoint of mechanical properties to mix the crushed molded article with the PAS resin composition. The size of the molded article when crushed is not particularly limited, but it is preferable that the size is about the same as that of the PAS resin composition to be mixed from the viewpoint of mixability and processability. In addition, the mixing ratio is preferably 50 parts by mass or less of the crushed molded article relative to 100 parts by mass of the PAS resin composition, more preferably 40 parts by mass or less, and even more preferably 20 parts by mass or less. In such a range, the recyclability can be improved without impairing the effect of the PAS resin composition of the present disclosure.
[0065] <Laminate and method for producing laminate> The laminate according to this embodiment is a laminate having a plating layer laminated on at least one surface of a molded article. The method for producing the laminate according to this embodiment includes a step of plating at least one surface of the molded article obtained by the above-described production method (hereinafter, sometimes simply referred to as a "plating step"). The method will be described in detail below.
[0066] The laminate according to the present embodiment may be a PAS resin molded article obtained by molding the PAS resin composition and having a roughened surface. The method for producing the laminate according to the present embodiment may include a step of roughening the surface of the PAS resin molded article obtained by molding the PAS resin composition by chemical etching (hereinafter, sometimes simply referred to as a "roughening step").
[0067] The roughening treatment step includes a step of contacting the surface of the PAS resin molded article with an etching solution, for example, by applying the etching solution by a dipping method. The etching solution is not particularly limited as long as it can remove the inorganic filler (B) present on the surface of the PAS resin molded article, but it is preferable that the etching solution contains a strong acid or a salt thereof. Examples of such strong acids or salts thereof include chromic acid, sulfuric acid, ammonium fluoride, nitric acid, and chromic anhydride, and one or more of these can be used in combination. The conditions for contacting the surface of the PAS resin molded article with the etching solution are preferably adjusted as appropriate, such as the concentration of the strong acid or its salt in the etching solution, the temperature during contact, and the time.
[0068] The etching solution may be a known one, for example, the one described in JP-A-5-155127, that is, an etching solution consisting of 400 g / L of sulfuric acid, 400 g / L of chromic anhydride, and dilution water (to make the total etching solution volume 1 L).
[0069] The roughening treatment step removes at least a part of the inorganic filler (B) uniformly dispersed on the surface of the PAS resin molded product, forming voids. The presence of these voids and the increase in the specific surface area further improve the interaction with the metal particles constituting the plating layer, and the adhesive strength between the PAS resin molded product and the plating layer is improved. In addition, in the past, when a coating film was formed with an adhesive or the like in the vertical direction of the molded product surface to adhere to the plating layer, the uncured adhesive or the like sagged under the influence of its own weight during production, causing deviations in the film thickness, which tended to cause unevenness in the adhesive strength. However, in the present invention, unevenness in the voids depending on the location on the molded product surface tends not to occur, and the adhesive strength is also excellent in uniformity. The surface roughness of the roughened surface of the PAS resin molded product is not particularly limited, but from the viewpoint of excellent adhesive strength, it is preferably 0.1 to 10 μm, more preferably 1 to 5 μm in terms of ten-point average roughness Rz.
[0070] The plating step includes a step of forming a plating layer made of metal and / or ceramics on the roughened surface of the PAS resin molded article by electroless plating, electrolytic plating, sputtering or a combination of these.
[0071] The electroless plating method is preferred because the metal or ceramic that constitutes the plating layer can be easily filled by the plating process into the voids formed on the roughened surface of the PAS resin molded article by removing the inorganic filler (B), thereby further improving the adhesion to the plating layer.
[0072] In the above-mentioned electroless plating method, for example, an electroless plating solution is brought into contact with the roughened surface of the PAS resin molded article, thereby precipitating metals such as copper contained in the electroless plating solution to form an electroless plating layer (film) consisting of a metal film.
[0073] The electroless plating solution may contain, for example, at least one metal selected from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, manganese, lithium, strontium, lanthanum, titanium, barium, zirconium, lead, and rhodium, a reducing agent, and a solvent such as an aqueous medium or an organic solvent.
[0074] Examples of the reducing agent include dimethylaminoborane, hypophosphorous acid, sodium hypophosphite, dimethylamineborane, hydrazine, formaldehyde, sodium borohydride, and phenol.
[0075] The electroless plating solution may contain, as necessary, a complexing agent such as a monocarboxylic acid, such as acetic acid or formic acid; a dicarboxylic acid compound, such as malonic acid, succinic acid, adipic acid, maleic acid or fumaric acid; a hydroxycarboxylic acid compound, such as malic acid, lactic acid, glycolic acid, gluconic acid or citric acid; an amino acid compound, such as glycine, alanine, iminodiacetic acid, arginine, aspartic acid or glutamic acid; an aminopolycarboxylic acid compound, such as iminodiacetic acid, nitrilotriacetic acid, ethylenediaminediacetic acid, ethylenediaminetetraacetic acid or diethylenetriaminepentaacetic acid; or a soluble salt (sodium salt, potassium salt, ammonium salt, etc.) of these organic acids, or an amine compound, such as ethylenediamine, diethylenetriamine or triethylenetetramine.
[0076] The electroless plating solution is preferably used at a temperature in the range of 20 to 98°C.
[0077] The electrolytic plating method is a method in which, for example, an electric current is passed through an electrolytic plating solution in contact with the surface of the electroless plating layer (film) formed by the electroless plating process, causing a metal such as copper contained in the electrolytic plating solution to precipitate on the surface of the electroless plating layer (film) formed by the electroless process, which is placed at a cathode, to form an electrolytic plating layer (film).
[0078] The electrolytic plating solution may, for example, contain at least one metal sulfate selected from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, manganese, lithium, strontium, lanthanum, titanium, barium, zirconium, lead, and rhodium, an acid, and an aqueous medium. Specifically, when a solution containing iron sulfate (II), nickel sulfate (II), boric acid, and an aqueous medium is used, a permalloy plating layer is obtained, which is preferable. When a permalloy layer is present, the magnetic permeability is high and good magnetic field shielding properties can be exhibited.
[0079] The electrolytic plating solution is preferably used at a temperature in the range of 20 to 98°C.
[0080] The sputtering method involves introducing an inert gas (mainly argon) into a vacuum, charging the PAS resin molded product as a positive electrode and the metal or ceramic material (target) that will form the plating layer as a negative electrode to generate a glow discharge, ionizing the inert gas atoms and slamming the gas ions into the target surface at high speed, ejecting the atoms and molecules that make up the target and causing them to adhere to the roughened surface of the PAS resin molded product, thereby forming a plating layer.
[0081] Examples of the sputtering method include bipolar sputtering, magnetron sputtering, dual magnetron sputtering, reactive sputtering, and ion beam sputtering, which can be used alone or in combination of two or more. The target application method can be any of DC (direct current) sputtering, DC pulse sputtering, AC (alternating current) sputtering, and RF (radio frequency) sputtering.
[0082] Examples of targets used in the sputtering method include targets containing at least one metal selected from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, manganese, lithium, strontium, lanthanum, titanium, barium, zirconium, lead, and rhodium, and permalloy, sendust, and ferrite are particularly preferred. When permalloy, sendust, and ferrite are contained in the plating layer, the magnetic permeability is high and good magnetic field shielding properties can be exhibited.
[0083] The thickness of the plating layer formed by the plating process is not particularly limited, but is, for example, preferably in the range of 0.1 μm or more and preferably 500 μm or less. The thickness of the plating layer formed by the plating process can be adjusted by the treatment time, number of treatments, current density, amount of plating additive used, etc. in the plating process.
[0084] The laminate of the present invention can also have a plating layer on at least two opposing sides of the PAS resin molded product. This allows it to exhibit better electric field shielding and magnetic field shielding properties than a laminate having a plating layer on only one side, even if the total plating thickness is the same. In addition, since the total plating thickness can be reduced, the amount of material used can be reduced, and the plating process time can be shortened.
[0085] In the laminate of the present invention, a plating layer is formed by plating treatment on the roughened surface of the PAS resin molded article, i.e., in the voids formed by removing the inorganic filler (B), and the plating layer, which is a thin film layer made of metal or ceramic, is adhered to the PAS resin molded article with high adhesive strength.
[0086] <Application> The PAS resin composition of the present disclosure has excellent processability, and the molded product is characterized by excellent plating adhesion, and is therefore particularly suitable for laminates having a plating layer. Specifically, it can be suitably used for electromagnetic shielding members, molded circuit components, etc. The molded product of the present disclosure is not limited to laminates, and can also be the following ordinary resin molded products. For example, protective and supporting members for box-shaped electric and electronic component integrated modules, multiple individual semiconductors or modules, sensors, LED lamps, connectors, sockets, resistors, relay cases, switches, coil bobbins, capacitors, variable capacitor cases, optical pickups, oscillators, various terminal boards, transformers, plugs, printed circuit boards, tuners, speakers, microphones, headphones, small motors, magnetic head bases, power modules, terminal blocks, semiconductors, liquid crystal displays, FDD carriages, FDD chassis, motor brush holders, parabolic antennas, computer-related parts, and other representative electric and electronic parts; VTR parts, television parts, irons, headsets, etc. Home and office electrical appliance parts such as air dryers, rice cooker parts, microwave oven parts, audio parts, audio / visual equipment parts such as laser discs, compact discs, DVD discs, and Blu-ray discs, lighting parts, refrigerator parts, air conditioner parts, typewriter parts, word processor parts, and water-related equipment parts such as water heaters, bath water volume and temperature sensors; office computer related parts, telephone related parts, facsimile related parts, copier related parts, cleaning jigs, motor parts, lighters, typewriters, and other machine related parts; optical equipment and precision machinery related parts such as microscopes, binoculars, cameras, and watches;Alternator terminals, alternator connectors, brush holders, slip rings, IC regulators, potentiometer bases for light dimmers, relay blocks, inhibitor switches, various valves such as exhaust gas valves, various pipes for fuel, exhaust and intake systems, air intake nozzle snorkels, intake manifolds, engine coolant joints, carburetor main bodies, carburetor spacers, exhaust gas sensors, coolant sensors, oil temperature sensors, brake pad wear sensors, throttle position sensors, crankshaft position sensors, temperature sensors, air flow meters, brake pad wear sensors, thermostat bases for air conditioners, heating hot air flow control valves, radiators Examples of automotive and vehicle related parts include brush holders for motors, water pump impellers, turbine vanes, wiper motor related parts, distributors, starter switches, ignition coils and bobbins, motor insulators, motor rotors, motor cores, starter relays, transmission wire harnesses, windshield washer nozzles, air conditioner panel switch boards, coils for fuel-related electromagnetic valves, fuse connectors, horn terminals, electrical component insulating plates, step motor rotors, lamp sockets, lamp reflectors, lamp housings, brake pistons, solenoid bobbins, engine oil filters, ignition device cases, and other various applications. EXAMPLES
[0087] The present invention will be described below using examples and comparative examples, but is not limited to these examples. In the following, unless otherwise specified, "%" and "parts" are based on mass.
[0088] <Examples 1 to 11 and Comparative Examples 1 to 5> (Production of PAS resin compositions and molded products) Each material was mixed according to the composition and mixing amounts shown in Table 1. The mixed materials were then fed into a vented twin-screw extruder "TEX-30α" manufactured by Japan Steel Works, Ltd., and melt-kneaded at a resin component discharge rate of 30 kg / hr, a screw rotation speed of 200 rpm, and a set resin temperature of 320°C to obtain pellets of the resin composition. The glass fiber was fed from the side feeder (S / T ratio 0.5), and the other materials were mixed uniformly in a tumbler beforehand and fed from the top feeder. The pellets of the obtained resin composition were dried in a gear oven at 140°C for 2 hours, and then injection molded to produce various molded products, which were then subjected to the following tests.
[0089] <Evaluation>
[0090] (1) Measurement of weight loss (amount of gas generated) A pellet sample of the resin composition was weighed into an aluminum dish of 4.00 g using a precision balance. The sample was left to stand in a dryer set at 150°C for 1 hour, then the dish was removed and allowed to cool to room temperature before being weighed. The dish was then left to stand in a dryer set at 325°C for 1 hour, then the dish was removed and allowed to cool to room temperature before being weighed. The weight loss of each sample was calculated using the following formula. The results are shown in Tables 1 and 2. Weight loss [wt%] = (Weight value after heating at 150°C [g] -Weight value after heating at 325°C [g]) / Weighing value after heating at 150°C [g] x 100
[0091] (2) Measurement of the amount of drowning Pellets of the resin compositions of Examples 1 to 11 and Comparative Examples 1 to 4 were used and fed to a Sumitomo Heavy Industries injection molding machine (SE75D-HP) with a cylinder temperature set to 310°C, and continuous injection molding was performed using a mold with a mold temperature controlled to 140°C. After the 10th shot was measured, the amount of drooling from the nozzle tip was measured for 30 seconds. The results are shown in Tables 1 and 2.
[0092] (3) Measurement of tensile strength The obtained pellets were fed into a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set at 310°C, and injection molding was performed using a mold for molding ISO Type-A dumbbell pieces with a mold temperature controlled at 140°C to obtain ISO Type-A dumbbell pieces. The resin was injected from a single gate to produce test pieces that did not include welds. The tensile strength of the obtained dumbbell pieces was measured using a measurement method based on ISO 527-1 and 2. The results are shown in Tables 1 and 2.
[0093] (4) Measurement of plating adhesion (adhesion) (Roughening process for PAS resin molded products) The obtained pellets were fed to a Sumitomo Heavy Industries injection molding machine (SE-75D-HP) with a cylinder temperature set to 310°C, and injection molding was performed using a mold for ISO D2 sheet molding with a mold temperature controlled to 140°C to obtain an ISO D2 sheet. The molded product was immersed in a chemical etching solution for 3 to 20 minutes, and then pulled out to form a roughened surface on the entire surface of the molded product. The chemical etching solution used was a chemical etching solution consisting of 400 g / L sulfuric acid, 400 g / L chromic anhydride, and dilution water (to make the total amount of etching solution 1 L).
[0094] (Plating process for PAS resin molded products) Next, the entire roughened surface of the PAS resin molded article obtained above was subjected to electroless copper plating by the following method. The product was immersed in an electroless copper plating solution (OIC Copper, pH 12.5, manufactured by Okuno Chemical Industries Co., Ltd.) at 55°C for 100 minutes to form an electroless copper plating film (thickness 2.5 μm). Next, the surface of the electroless copper plating obtained above was thoroughly washed, and then immersed in an electroless nickel plating solution (Top Nicoron SA-98, pH 9, manufactured by Okuno Chemical Industries Co., Ltd.) at 30°C for 3 minutes to form an electroless nickel plating film (thickness 0.25 μm).
[0095] (Cross-cut test) A cross-cut test was carried out on the plated surface formed by the above method using adhesive tape specified in JIS Z 1522 (adhesive strength: approximately 8 N per 25 mm width, nominal width: 12-19 mm, Cellotape (registered trademark) No. 405 manufactured by Nichiban Co., Ltd.). First, a sharp blade was used to create marks on the plated surface that reached down to the base material, creating 5 x 5 = 25 squares with sides of 2 mm. The center of the tape was placed on top of the squares, leaving 30-50 mm of the tape edge not attached to the base material, and the tape was applied flat with a finger. At this time, care was taken to avoid the formation of air bubbles, and the tape was applied with a pressure of 20 N / cm 2 The tape was pressed firmly for approximately 10 seconds with a knife. Within one minute, the end of the tape that remained unattached was held and peeled off at a speed of 200 cm / sec at a 90° angle to the plated surface. In the table, "0 / 25" means that 0 squares peeled off, and "25 / 25" means that 25 squares peeled off. The fewer the peeled surfaces out of the 25 squares, the greater the adhesive strength is evaluated to be. The evaluation results are shown in Tables 1 and 2.
[0096] [Table 1]
[0097] [Table 2]
[0098] <Raw materials used> The raw materials of the PAS resin composition and the components that make up the plating layer are shown below. ·PPS resin (A-1) Linear type, melt viscosity (V6) 8 Pa·s, non-Newtonian index 0.98, weight average molecular weight 23,000 (A-2) Linear type, melt viscosity (V6) 20 Pa·s, non-Newtonian index 1.02, weight average molecular weight 28,000 (A-3) Linear type, melt viscosity (V6) 70 Pa·s, non-Newtonian index 1.05, weight average molecular weight 38,000 ·Calcium carbonate (B-1) Product name "KRS-1", manufactured by Maruo Calcium Co., Ltd., synthetic calcium carbonate surface-treated with calcium phosphate, mass loss rate at 100 to 350°C = 0.2% (B-2) Product name "CALUCEO P015S0", manufactured by Shiraishi Kogyo Co., Ltd., synthetic calcium carbonate surface-treated with a silane coupling agent, mass loss rate at 100 to 350 ° C = 0.4% (b-3) Product name "YM-10", manufactured by Maruo Calcium Co., Ltd., synthetic calcium carbonate surface-treated with fatty acid ester, mass loss rate at 100 to 350°C = 0.1% (b-4) Product name "NS-2300", manufactured by Nitto Funka Kogyo Co., Ltd., crushed heavy calcium carbonate without surface treatment agent, mass reduction rate = 0.0% Elastomer (C-1) Product name "BondFast 7L", manufactured by Sumitomo Chemical Co., Ltd. (C-2) Product name "MX Nylon #6000", manufactured by Mitsubishi Gas Chemical Company, Inc. (C-3) Product name: "UBE Nylon 1030B", manufactured by Ube Industries, Ltd. (C-4) Product name: "Unitika Nylon 66 ET2025", manufactured by Unitika Ltd. (C-5) Product name "Leona 1402S", manufactured by Asahi Kasei Corporation (C-6) Product name "AMODEL A-1004", manufactured by Amodel Specialty Polymers Glass fiber (D-1) Product name "T-717H", manufactured by Nippon Electric Glass Co., Ltd., fiber length 3 mm, average diameter 10 μm
[0099] The particle size of each calcium carbonate is shown in Table 3.
[0100] [Table 3]
[0101] From the results of Tables 1 and 2, comparing the Examples and Comparative Examples, it is seen that the evaluations of weight loss and drowning change significantly depending on the type of surface treatment agent for calcium carbonate. Also, when there is no surface treatment agent for calcium carbonate, weight loss and drowning are rated as good, but it is seen that the small particle size of calcium carbonate significantly changes the plating adhesion. It was shown that when the amount of calcium carbonate blended is small, the amount of drowning increases and the plating adhesion also deteriorates.
Claims
1. A polyarylene sulfide resin composition comprising a polyarylene sulfide resin (A) and an inorganic filler (B) as essential components, The inorganic filler (B) is calcium carbonate surface-coated with a silane coupling agent or an inorganic acid, and has a cumulative 90% particle diameter (D 90 ) is 3 μm or less, The polyarylene sulfide resin composition has an inorganic filler (B) content of 50 to 150 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A).
2. 2. The polyarylene sulfide resin composition according to claim 1, wherein the inorganic filler (B) is calcium carbonate synthesized by a carbon dioxide gas method.
3. The inorganic filler (B) has a cumulative 90% particle diameter of the particle size distribution (D 90 ), cumulative 50% particle diameter (D 50 ) and cumulative 10% particle size (D 10 ) to obtain the following formula (1): (D 90 -D 10 ) / D 50 <2.0 … (1) The polyarylene sulfide resin composition according to claim 1 or 2, wherein the polyarylene sulfide resin composition is represented by the formula:
4. The polyarylene sulfide resin composition according to any one of claims 1 and 2, wherein the inorganic filler (B) has a mass loss rate of 1 mass% or less at 100 to 350 ° C.
5. A molded article obtained by melt molding the resin composition according to claim 1 or 2.
6. A laminate comprising the molded article according to claim 5 and a plating layer laminated on the surface thereof.
7. A method for producing a polyarylene sulfide resin composition, comprising a step of blending a polyarylene sulfide resin (A) and an inorganic filler (B) as essential components, and melt-kneading the mixture at a temperature range equal to or higher than the melting point of the polyarylene sulfide resin (A), The inorganic filler (B) is calcium carbonate surface-coated with a silane coupling agent or an inorganic acid, and has a cumulative 90% particle diameter (D 90 ) is 3 μm or less, The method for producing a polyarylene sulfide resin composition, wherein the blending amount of the inorganic filler (B) is 50 to 150 parts by mass per 100 parts by mass of the polyarylene sulfide resin (A).
8. 8. The method for producing a polyarylene sulfide resin composition according to claim 7, wherein the inorganic filler (B) is calcium carbonate synthesized by a carbon dioxide gas method.
9. The inorganic filler (B) has a cumulative 90% particle diameter of the particle size distribution (D 90 ), cumulative 50% particle diameter (D 50 ) and cumulative 10% particle size (D 10 ) to obtain the following formula (1): (D 90 -D 10 ) / D 50 <2.0 … (1) The method for producing the polyarylene sulfide resin composition according to claim 8, wherein the polyarylene sulfide resin composition is represented by the formula:
10. The method for producing a polyarylene sulfide resin composition according to any one of claims 7 and 8, wherein the inorganic filler (B) has a mass reduction rate of 1 mass% or less at 100 to 350 °C.
11. A method for producing a molded article, comprising the steps of producing a polyarylene sulfide resin composition by the production method according to claim 7 or 8, and melt-molding the obtained polyarylene sulfide resin composition.
12. A method for producing a laminate, comprising the steps of producing a polyarylene sulfide resin molded article by the method according to claim 11, and plating a surface of the obtained molded article.
Citation Information
Patent Citations
Metal plating treatment
JP1988014880A
Polyarylene sulfide resin composition, and polyarylene sulfide film
JP2009249492A
Polyarylene sulfide-based composition
JP2016132710A
Resin composition for plating, resin molded body for plating, and resin molded body with plating film
JP2020066644A
Calcium carbonate filler for resins, and resin composition containing same
WO2018088008A1